Running to get “lost”? Two types of escapism in recreational running and their relations to exercise dependence and subjective well-being - Stenseng, Frode; Steinsholt, Ingvild Bredvei; Hygen, Beate Wold; Kraft, Pål (Frontiers in Psychology, 2023)
Escapism is a fundamental motivation in many forms of activity engagements. At its core, escapism is “a habitual diversion of the mind . . . as an escape from reality or routine” (Merriam-Webster, n.d.). Accordingly, escapism may entail many adaptive and maladaptive psychological antecedents, covariates, and outcomes. However, few studies have been conducted on escapism as a motivational mindset in running. Here, in a sample of recreational runners (N = 227), we applied a two-dimensional model of escapism (Stenseng et al., 2012), comprising self-expansion (adaptive escapism) and self-suppression (maladaptive escapism), and examined how they were related to exercise dependence and subjective well-being. First, confirmatory factor analyses showed that the escapism dimensions were highly diversifiable in the sample. Then, correlational analyses showed that self-expansion was positively correlated to subjective well-being, whereas self-suppression was negatively related to well-being. Self-suppression was more strongly related to exercise dependence compared to self-expansion. Finally, path analyses evidenced an explanatory role of self-expansion and self-suppression in the inverse relationship between exercise dependence and well-being. In conclusion, the present findings support escapism as a relevant framework for understanding the relationship between exercise dependence in running and subjective well-being.